Pharmacokinetic, partial pharmacodynamic and initial safety analysis of (−)-epicatechin in healthy volunteers1. Issue 3 (11th March 2015) - Barnett, Christopher F.; Moreno-Ulloa, Aldo; Shiva, Sruti; Ramirez-Sanchez, Israel; Taub, Pam R.; Su, Yongxuan; Ceballos, Guillermo; Dugar, Sundeep; Schreiner, George; Villarreal, Francisco
<x xml:space="preserve">Abstract</x> (−)-Epicatechin ((−)-EPI), a naturally occurring flavanol, has emerged as a likely candidate for cocoa-based product reported reductions in cardiometabolic risk.